Factors Affecting Prenatal Care Utilization in East Wollega Zone, Oromia Regional State, Ethiopia - Regassa, T; Agero, G (Science, technology and arts research, 2014)
The objective of the study was to identify factors affecting utilization of prenatal care and skilled birth attendant in East Wollega zone. Prenatal care and skilled birth attendant are crucial factor which affects the health and wellbeing of the mother and newborn and help the women to access skilled assistance, drugs, equipment and referral linkages. Even though, antenatal care coverage was relatively high in Oromia region, skilled birth attendant utilization was low. A total of 320 respondents were included in the study and data were collected using structured questionnaires. Data were first checked manually for completeness and then coded and entered into Epi Info version 6.04 and analyzed using SPSS version 20.0. Bivariate analyses between dependent and independent variable was performed using binary logistic regression separately. The study highlight that housewives were less likely to receive prenatal care from skilled professionals. Another predictor of prenatal care was having functional communication materials. Longer waiting time at health institutions was significantly associated with prenatal care. Reported skill of health care providers were significantly associated with prenatal care.